Efeito da crioterapia na propriocepção dos músculos do assoalho pélvico em mulheres com incontinência urinária de esforço: ensaio clínico randomizado controlado - Silva, Denise Rodrigues da (2020)
Introduction: Some women with urinary incontinence (UI) are unable to correctly contract the pelvic lining (PFM) muscles properly, requiring the use of proprioceptive measures. Cryotherapy is an accessible and low-cost resource capable of providing muscle tremors, however, there are studies that assess whether the body's thermoregulatory response helps in the proprioception of MAP. Objective: Compare the effect between cryotherapy and manometry in the maximum voluntary contraction of PFM, analyze the temperature variation of the tendon center (TC) after the application of both interventions and compare the level of satisfaction of the volunteers after the application of these methods. Materials and methods: Randomized controlled clinical trial, with 33 participants older than 35 years, with SUI complaint. The participants performed anamnesis, including sociodemographic, urogynecological and obstetric data, then the incontinence severity index questionnaire (ISI-Q) was applied. In the physical evaluation, the one-hour absorbing test was performed, assessment of the maximum voluntary contraction of the PFMs through manometry and assessment of the function of the PFMs with the PERFECT scheme. After 48 hours of the evaluation, the volunteers were randomized: 17 volunteers started the intervention in the Cryotherapy Group (CG) and after 48 hours they were part of the Manometry Group (MG); 16 volunteers started in the manometry group (MG) and after 48 hours they underwent intervention in the CG. The temperature was assessed in the TC using the Digital Infrared LASER Thermometer GM320 in the following moments: before the application of the intervention, immediately after the interventions and in the 1st, 2nd and 5th minutes after. Then measuring the temperature, the initial evaluator was invited to reassess the capacity of the maximum voluntary contraction of MAP, manometry and satisfaction with the treatment. Statistical analysis: The power of the sample was calculated using Gpower software version 3.1.9.2, for the sample of 33 individuals in each group, a power of 64% was detected. The Wilcoxon test was used for intragroup analysis and the Mann-Whitney test for intergroup analysis. The level of significance adopted was 5%. Results: CG showed an increase in all stages of PERFECT and in the 2nd measurement of manometry after the intervention (p=0.032). In the GM there was a significant increase in the PERFECT power stage (p=0.023) and in the 1st manometry measure (p=0.015), however there was no significant difference in the intergroup analysis. As for satisfaction, the CG and GM did not show significant differences (p = 0.3083), and the GC showed a decrease in temperature immediately after application and on the 1st, 2nd and 5th minutes after intervention (p=0.0001). Conclusion: The CG showed improvement in the function and pressure of MAP contraction, however this intervention did not present better results when compared with manometry. Satisfaction levels after intervention are similar, demonstrating that a decrease in temperature during cryotherapy did not influence patient satisfaction.